SE STRATEGI PENDIDIKAN AGAMA HINDU DALAM MEMBANGUN KARAKTER DAN MORALITAS PADA SISWA MELALUI SUSATRA HINDU : STRATEGI PENDIDIKAN AGAMA HINDU DALAM MEMBANGUN KARAKTER DAN MORALITAS PADA SISWA MELALUI SUSATRA HINDU - Adi, Eko adi saputra (JAPAM (Jurnal Pendidikan Agama), 2024)
The young generation as agents of change in nation building needs basic guidelines in overcoming the negative effects of globalization. Technological developments which are growing very rapidly are able to show very significant changes in all aspects of life. Therefore, teachings are needed as a guide to behavior in an effort to build morality and good character, namely moral teachings. According to the Hindu religious view, morality is a reciprocal and harmonious behavior between human beings and the universe (environment) which is based on compassion, sincerity and compassion. Through Character and Morality Education at school is education that strives for good ethics, mutual respect and respect for differences between students and teachers at school. This research describes how Hindu literature strategies in building students' character and morals through Hindu religious education. The young generation or what is known as generation Z as agents of change in nation building need basic guidelines in overcoming the negative influences of globalization. Technological developments are able to show very significant changes in everything. aspect of life. Therefore, teachings are needed as a guide to behavior in an effort to build morality and good character, namely moral teachings. According to the Hindu religious view, morality is a reciprocal and harmonious behavior between human beings and the universe (environment) which is based on compassion, sincerity and affection between God's creatures.